MIGRATION AND SOCIAL CHANGES OF ETHIC BUGIS IN KUPANG CITY, INDONESIA - Tang B. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The ethnic Bugis migration to Kupang besides being a source of income, also as a means or means that determine access to resources power in city Kupang. Various dynamics encourage a number of people to migrate permanently to the city of Kupang. This study aims to identify the motives for migration and social change in the people of Kupang. This study was conducted at Kota Kupang East Nusa Tenggara by using a qualitative approach. Her results showed that the migration of ethnic motif Bugis because of the driving factors originating from the area of origin and the pull factors that are in the city of Kupang. The driving factor consists of low income as a result of lack of employment opportunities in the area of origin. Factors above are where broader employment opportunities, and high income and wages. Ethnic Bugis the profession trader has spawned a new social class in the structure of society. The social class of the merchant consists of the upper class (Large merchant group), middle class (medium merchant group), lower class (retailer group).